Branding TPA Wisata Edukasi Talangagung Kabupaten Malang - Cheryke Selsa Adia; Pujiyanto Pujiyanto; Fariza Wahyu Arizal (LPPM STIKI Malang, 2019)
The purpose of branding design as an effort to improve the brand image is to get to know and attract consumers' interest to come to Talangagung Education Tourism Landfill. The method used in this design is to use qualitative methods by conducting observations, interviews, documentation, and questionnaires. This needs to be done in order to collect supporting data for the preparation of branding design concepts. So the design of this branding is done with a unique and interesting visual form that can be applied to promotional media so as to form the brand image of the Talangagung Education Tourism Landfill. The result of this design changed branding is the logo as the main identity that is designed based on the identity of the Talangagung Education Tourism Landfill. Besides that, it is equipped with other supporting media.